A perfusion bioreactor system efficiently generates cell‐loaded bone substitute materials for addressing critical size bone defects. Issue 11 (24th June 2015) - Kleinhans, Claudia; Mohan, Ramkumar Ramani; Vacun, Gabriele; Schwarz, Thomas; Haller, Barbara; Sun, Yang; Kahlig, Alexander; Kluger, Petra; Finne‐Wistrand, Anna; Walles, Heike; Hansmann, Jan
Abstract: Critical size bone defects and non‐union fractions are still challenging to treat. Cell‐loaded bone substitutes have shown improved bone ingrowth and bone formation. However, a lack of methods for homogenously colonizing scaffolds limits the maximum volume of bone grafts. Additionally, therapy robustness is impaired by heterogeneous cell populations after graft generation. Our aim was to establish a technology for generating grafts with a size of 10.5 mm in diameter and 25 mm of height, and thus for grafts suited for treatment of critical size bone defects. Therefore, a novel tailor‐made bioreactor system was developed, allowing standardized flow conditions in a porous poly(L‐lactide‐co‐caprolactone) material. Scaffolds were seeded with primary human mesenchymal stem cells derived from four different donors. In contrast to static experimental conditions, homogenous cell distributions were accomplished under dynamic culture. Additionally, culture in the bioreactor system allowed the induction of osteogenic lineage commitment after one week of culture without addition of soluble factors. This was demonstrated by quantitative analysis of calcification and gene expression markers related to osteogenic lineage. In conclusion, the novel bioreactor technology allows efficient and standardized conditions for generating bone substitutes that are suitable for the treatment of critical size defects in humans. Abstract : Bioreactor technology allows generating cell‐loaded bone substitute materials for the treatment of critical size bone defects. Cultured scaffolds exhibit a homogeneous cell distribution and dynamic culture conditions enhance calcification and expression of osteogenic‐related genes. The major advantage of the technology is that the mechanical stimulation supports omitting soluble factors for triggering osteogenic differentiation.